(untitled) (Sustainability in Debate, 2011)
The goal of this paper is to analyse the concept of natural heritage in transboundary spaces. After introducing the concept of natural heritage, we discuss its implication in the Paraguay watershed. In fact there is a clash between natural and political spatial unities. We argue that patrimonialisation/territorialisation provide a new institutional framework to the south America regional integration.